The Influence of Organizational Culture, Work Discipline, and Work Experience on Employee Performance at PT Sinarmulia Sukses Makmur - Gusvarizon, Muhammad; Ningsih, Putu Tirta Sari; Fadliah, Siti (Universitas Mohammad Husni Thamrin, 2025)
Human resource management plays an active role in improving employee performance through a number of influencing variables including organizational culture, work discipline, work experience and employee performance. This research is a quantitative research with a descriptive design. The research was conducted by seeking primary data, through questionnaires filled out by respondents of PT. Sinarmulia Sukses Makmur employees, which were conducted by sampling through a random sampling method. The data were processed by statistical analysis with multiple linear regression tests, coefficient of determination (adjusted Rsquare), partial hypothesis testing (t-test) and simultaneous ANOVA testing (F-table). The objectives of this study are: 1) To determine the effect of organizational culture on employee performance. 2) To determine the effect of work discipline on employee performance. 3) To determine the effect of work experience on employee performance. 4) To determine the effect of organizational culture, work discipline and work experience together on employee performance of PT. Sinarmulia Sukses Makmur. The results of this study are as follows: 1) Organizational culture has a significant effect on employee performance. 2) Work discipline has a significant effect on employee performance. 3) Work experience has a significant effect on employee performance. 4) Organizational culture, work discipline and work experience together have a significant influence on the performance of PT. Sinarmulia Sukses Makmur employees. The conclusion of this study is that there is a significant influence between organizational culture, work discipline, work experience and employee performance at PT. Sinarmulia Sukses Makmur.